Effects of the Single Market on the Austrian Insurance Industry - Bernhard Mahlberg; Thomas Url (Austrian Institute of Economic Research (WIFO), 1998)
The integration of European services markets and the associated deregulation measures open up formerly segmented markets to competition from the Single Market. The purpose of this study is to propose a method of measuring the effects of liberalization on technical efficiency, the existence of economies of scale and diversification, and the dynamic development of productivity for the insurance industry. As an example we construct efficiency frontiers for the years 1992 through 1996 for the Austrian insurance industry using a Data Envelopment Analysis. The results provide yardsticks for efficiency comparisons from a consumer perspective and can be used to construct a Malmquist productivity index for the transition period.
Keywords: L50; G22; C14; 330; European Integration; Insurance Industry; Data Envelopment Analysis; Versicherung; Österreich